L'ambiguïté dans l'emploi du relatif-interrogatif en ancien français - Velinova, Malinka (My University, 2009)
The paper examines some aspects of the ambiguity caused by the distance between the wh- words and the antecedent in French medieval texts (from the beginning of the 12th to the middle of the 13th century). Uncertainty can appear when the wh- word's referent or when the relative clause type (i.e. restrictive versus non-restrictive) has to be recognised. The ambiguity induced by the polysemy of the forms has also been given consideration. An attempt has been made to determine how the enunciation in praesentia, i.e. the oral or to-be-read-aloud character of the texts, affects the disjunction phenomenon-generated referential instability – from the viewpoints of both contemporary and medieval reader.